Strain Gradient Programming in 3D Fibrous Hydrogels to Direct Graded Cell Alignment (Small Methods 1/2023). Issue 1 (17th January 2023) - Kolel, Avraham; Ergaz, Bar; Goren, Shahar; Tchaicheeyan, Oren; Lesman, Ayelet
Abstract : Inside Front Cover In article number 2201070, Lesman and co‐workers use controlled geometry and external stretch to generate programmable gradients in strain and fiber alignment across 3D biological gels, leading to spatial controlled over cell alignment patterns. It provides a new technology for mechanobiology and tissue engineering applications.